Drosophila peptidoglycan recognition protein LC (PGRP-LC) acts as a signal-transducing innate immune receptor - Choe, Kwang-Min (National Academy of Sciences, 2005)
Drosophila peptidoglycan recognition protein LC (PGRP-LC), a transmembrane protein required for the response to bacterial infection, acts at the top of a cytoplasmic signaling cascade that requires the death-domain protein Imd and an IκB kinase to activate Relish, an NF-κB family member. It is not clear how binding of peptidoglycan to the extracellular domain of PGRP-LC activates intracellular signaling because its cytoplasmic domain has no homology to characterized proteins. Here, we demonstrate that PGRP-LC binds Imd and that its cytoplasmic domain is critical for its activity, suggesting that PGRP-LC acts as a signal-transducing receptor. The PGRP-LC cytoplasmic domain is also essential for the formation of dimers, and results suggest that dimerization may be required for receptor activation. The PGRP-LC cytoplasmic domain can mediate formation of heterodimers between different PGRP-LC isoforms, thereby potentially expanding the diversity of ligands that can be recognized by the receptor.